Mumbai Metro transforming transport contributing toward an equitable, safer, and cleaner city. (Sustainable development working papers., 2021)
Mumbai is the financial capital of India and one of the worlds most densely populated cities. The Mumbai Metro will provide equal access for all to a modern, comfortable, and high quality daily commuting transport option. It will feature safety designs (especially for the vulnerable sectors), ease traffic congestion, and reduce vehicular emissions, thereby contributing toward making Mumbai a more equitable, safer, and cleaner city.